F119. Presence of TcMEPs in the setting of acute clinical paraplegia. (May 2018) - Parikh, Pooja; Shilian, Parastou; Cheongsiatmoy, Justin; Gonzalez, Andres A.
Abstract : Introduction: In surgeries where neural structures are at risk, Intraoperative neurophysiological monitoring (IONM) provides insight into the integrity of the nervous system. Each patient serves as his or her own control, and baselines obtained at the beginning of the surgery provide a comparative standard for subsequent signals. The process of establishing controls is necessary to determine the presence and degree of potential intraoperative changes. Unfortunately, adequate baselines are sometimes unattainable due to preexisting neurological deficits. Patients with acute spinal cord injury and complete motor loss often demonstrate absence of transcranial motor evoked potentials (TcMEPs) below the level of the lesion. We are presenting a case of a 62-year-old man with traumatic L1 burst fracture and subsequent acute lower extremity paralysis (ASIA B) who underwent emergent surgical decompression and spinal fusion. TcMEPs were present despite absent of clinical movement in the bilateral lower extremities. Methods: Total intravenous anesthesia was administered via propofol and remifentanil drip. No neuromuscular blockade was given. The patient was turned to the prone position for surgery. Intraoperative monitoring was performed using the Cascade Elite system by Cadwell. We placed 13 mm paired subdermal disposable needle electrodes in the intrinsic hand muscles, quadriceps femoris, tibialis anterior, gastrocnemius and intrinsic foot muscles. We placed corkscrew electrodes at C1 and C2 to deliver transcranial stimulation. Baseline TcMEPs were obtained using the following stimulation parameters: 7 pulses, 3 ms inter-stimulus interval, 400-volt intensity. The MEP recording bandpass was 30–2000 Hz and gain was set at 500 mcv/div. Results: Baseline TcMEPs were obtained three hours after initial injury. Despite compelete paraplagia on preoperative exam, baseline TcMEP responses were present and robust in the bilateral quadriceps and tibialis anterior muscles, while small and variable in the bilateral intrinsic feet muscles. These aforementioned potentials remained unchanged throughout the procedure. On subsequent post-operative physical examinations, the patient regained motor strength in lower extremity muscles that were initially present on the baseline. Specifically, recovery of motor strength was greater in the proximal lower extremity muscles compared to their in distal counterparts. Conclusion: TcMEPs can be present in the acute spine injury patient despite absent of motor response on clinical examination. We postulate that intraoperative TcMEP baselines in acute spinal cord injury patients with severe motor deficits may potentially be used as a predictor of post-operative clinical outcome.